2010
DOI: 10.1002/cbic.201000256
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Internalization of Water‐Soluble Helical Aromatic Amide Foldamers

Abstract: The intracellular transport of drugs and therapeutics represents one of the most exciting and challenging areas at the interface of chemistry, biology, and medicine. Most of the effort in this field so far has been devoted to the development of peptide-based delivery systems that can translocate therapeutic agents into their intracellular targets. More recently, the use of bioinspired non-natural foldamers has resulted in the successful delivery of cargo molecules, which possess a wide range of sizes and physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 67 publications
0
37
0
2
Order By: Relevance
“…It emerged that a minimum chain length and number of basic side-chains are necessary for efficient cell internalization. The oligomer with octameric chain length exhibited excellent penetration abilities in the HeLa, Huh-7 and Jurkat cell-lines too [81]. Importantly, these oligomers were nontoxic even in high concentrations.…”
Section: Cell-penetrating Foldamersmentioning
confidence: 95%
See 1 more Smart Citation
“…It emerged that a minimum chain length and number of basic side-chains are necessary for efficient cell internalization. The oligomer with octameric chain length exhibited excellent penetration abilities in the HeLa, Huh-7 and Jurkat cell-lines too [81]. Importantly, these oligomers were nontoxic even in high concentrations.…”
Section: Cell-penetrating Foldamersmentioning
confidence: 95%
“…Importantly, these oligomers were nontoxic even in high concentrations. Lowtemperature experiments suggested that the uptake is an endocytosis-dependent process [81]. All the oligomers formed stable helical structures, which is important from the aspect of the biological function.…”
Section: Cell-penetrating Foldamersmentioning
confidence: 99%
“…Second, the same procedures serve, after some adjustments, to produce variants having other side chains than isobutoxy groups, including water-solubilizing side chains (see Experimental design). For example, a variant of the helical octamer bearing ornithine-like ammonium side chains shows promise for several biological applications [27][28][29][30] , and a variant bearing oligoethylene oxide side chains was recently prepared to be endowed with solubility in a broad range of media 32 . Anionic, aspartate-like side chains have been introduced as well 30,33 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, amphipathic aryl amide oligomers have been fine-tuned to show selective antimicrobial activity 23 or to interfere with heparin function 24 . Linear aryl amides have been used as α-helix mimetics designed to disrupt protein-protein interactions 25,26 , and helical oligomers bearing cationic side chains feature cell-penetrating properties 27,28 and selective binding to G-quadruplex DNA 29,30 .…”
Section: Introductionmentioning
confidence: 99%
“…Another advantage is that their helical shape is extremely predictable, and since monomer side-chains may be positioned away from the backbone amide motifs, folding is essentially independent of R-group functionality. This allows the display of arrays of side-chains to be tuned in order to optimize interactions with a specific biomolecule, affording foldamers with cell-penetrating properties (Gillies et al, 2007;Iriondo-Alberdi, Laxmi-Reddy, Bouguerne, Staedel & Huc, 2010), high affinity for G-quadruplex DNA (Delaurière, Dong, Laxmi-Reddy, Godde, Toulmé & Huc, 2012;Müller, Laxmi-Reddy, Jena, Baptiste, Dong, Godde et al 2014), or the potential to interact with protein surfaces. (Buratto, Colombo, Stupfel, Dawson, Dolain, Langlois d'Estaintot et al 2014).…”
Section: Introductionmentioning
confidence: 99%